Identity and identification Proceedings of the 14th international "Culture and Power" conference - Mateos-Aparicio Martin-Albo, Ángel; Gregorio Godeo, Eduardo de (ESTUDIOS, 2017)
The present volume includes the Proceedings of The 14 th International Culture and Power Conference, organized by the University of Castilla-La Mancha and held in Ciudad Real, Spain, between 22 and 24 March, 2010 under the auspices of The Iberian Association for Cultural Studies (IBACS). The collection incorporates a selection of the papers presented. The conference revolved around the topic of identity and identification, which, in the contributions, is explored in various cultural products across a wide range of social and national contexts. Identity and identification processes are examined as interrelated with other social and cultural dimensions. Readings echo a multiplicity of theoretical approaches, the number of issues contemplated being representative of the relevance of identity and identification processes as crucial analytical perspectives for cultural studies today.